The regulatory effect of flavonoids extracted from Abutilon theophrasti leaves on gene expression in LPS-induced ALI mice via the NF-κB and MAPK signaling pathways - Chunlian Tian; Xiaoyun Chen; Yu Chang; Ruxia Wang; Jing Ning; Cancan Cui; Mingchun Liu (Taylor & Francis Group, 2019)
Context: ALI is a common disease characterized by acute pulmonary inflammatory disorder. Abutilon theophrasti Medik. (Malvaceae), as a Chinese traditional medicine, is used for the treatment of inflammation. Its main constituents are flavonoid compounds. Objective: This study investigates the regulatory effect of a TFE from Abutilon theophrasti leaves on gene expression in LPS-induced ALI mice via the NF-κB and MAPK signaling pathways. Materials and methods: Kunming mice were intragastrically administered TFE (0.25, 0.5, 1.0 g/kg) for 5 days, and then ALI was induced via intranasal administration 40 μg of LPS in 10 μL PBS after intragastric administration on the 5th day, and PBS and DEX (2 mg/kg) were negative and positive control groups, respectively. Results: The relative expression of iNOS gene was 0.707, 0.507 and 0.483 for 0.25, 0.5 and 1.0 g/kg TFE, and COX-2 gene expression was also reduced after treatment by three concentrations of TFE with 0.768, 0.545, and 0.478. The mRNA expression levels of p65 were 0.61, 0.43 and 0.27 for 0.25, 0.5 and 1.0 g/kg TFE and IκB levels were increased in a dose-dependent manner with 3.99, 13.69 and 34.36. 0.5 and 1.0 g/kg TFE inhibited the expression of ERK1/2 with 0.59 and 0.38, p38MAPK with 0.62 and 0.54, and JNK with 0.37 and 0.29, and JNK mRNA expression was 0.60 for 0.25 g/kg TFE. Discussion and conclusion: These results indicate that the regulatory mechanisms of TFE on gene expression in LPS-induced ALI mice include inhibition of the NF-κB and MAPK signaling pathways.